2016
DOI: 10.1161/hypertensionaha.115.06360
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Risk Subsequent to Gestational Dysglycemia Is Modified by Race/Ethnicity

Abstract: Gestational diabetes mellitus is associated with an increased risk of type 2 diabetes mellitus and hypertension. Additionally, gestational dysglycemia has been associated with an increased risk of type 2 diabetes mellitus but not yet associated with hypertension subsequent to pregnancy in long-term follow-up. Therefore, we set out to examine this relationship as well as the role of race/ethnicity in modifying this relationship. We analyzed a prospective observational cohort followed between 1998 and 2007. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…We found that race/ethnicity was the stronger predictor of postpartum cardio-metabolic risk, with African American and Latina women having higher postpartum cardio-metabolic risk as compared to White women. Presence of a prenatal cardio-metabolic disease further increased this risk, which is consistent with past research (Bentley-Lewis, et al, 2016; Bentley-Lewis, et al, 2014; Kousta, et al, 2006). This highlights differences in disease risk and burden experienced by African American and Latina women.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that race/ethnicity was the stronger predictor of postpartum cardio-metabolic risk, with African American and Latina women having higher postpartum cardio-metabolic risk as compared to White women. Presence of a prenatal cardio-metabolic disease further increased this risk, which is consistent with past research (Bentley-Lewis, et al, 2016; Bentley-Lewis, et al, 2014; Kousta, et al, 2006). This highlights differences in disease risk and burden experienced by African American and Latina women.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, low SES has also been associated with increased risk for developing cardio-metabolic diseases in pregnancy (Silva, et al, 2008; Steegers, et al, 2010). Despite these findings, few studies examine all three risk factors together, and only three studies have explored whether race/ethnicity and prenatal cardio-metabolic diseases interact in predicting risk of postpartum cardio-metabolic health (Bentley-Lewis, Huynh, Li, Wenger, & Thadhani, 2016; Bentley-Lewis, et al, 2014; Kousta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity (reported as BMI over 30 in this study) and ethnicity have previously been reported as risk factors [20,21]. Yet, in this study those factors were not statistically significant as predictors for gestational hypertension.…”
Section: Discussioncontrasting
confidence: 54%